Factors Involved in Selecting Health Services and Products - Aleke, Christian; Nwankwo, Beatrice (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Health services and products are of paramount importance at reforming and improving the performance of health system. The selection of health services and products should be based on the therapeutic needs of the health care system. This paper focuses on the factors involved in selecting health services and products. Various ailments /indications, definitions and products recommendations were identified and some factors for selecting various health products and health services were also reviewed. Claims about health products can be persuasive and misleading. This paper has been designed so that individual, community, health care givers or professionals, government and the general public can learn to evaluate information about health products, especially those that target the youth market.Thus health services and products are those self growth tools for those seeking to improve their health and wellness through herbal supplement, over -the-encounter drugs, mental enrichment, and physical fitness product (such as exercycle exercise), arthro-aquatic fitness system, treadmills, total-body elliptical crosstrainers, wheel chair bike. The individual, community, government, health care givers or professionals and the general public were advised to be equipped and guided by these factors in selecting their physical health services and products in order to achieve sound physical, mental emotional and social well being. Hence, this group of people is consumers of a range of health products and services throughout their lives, it is important that as they gain the knowledge and skills to choose those that will best meet their health needs.